Pemikiran Islam Wasathiyah Hasan Al Bashri - Ahmad Hanif Fahruddin; Mufid Murtadlo, Abdul; Nur Syarifuddin (Akademika, 2024)
Hasan Al Basrhi's thoughts on the moderation of Sufism have a strong tendency towards tawasuh or moderate. Perhaps some people think that tasawu tends to direct oneself to isolate oneself with worldly frenzy so that it seems as if there is a non-reactive attitude to the surrounding conditions. But on the contrary, Hasan Al Bahsri restored the essential spirit of Sufism as a moderate religious teaching and helped shape paradigms, thinking patterns, action patterns and wasathiyah behavior patterns.